MODELING THE PROCESS OF ECOLOGIZATION INVESTMENTS IN ENERGY SAVING IN RESIDENTIAL AND PUBLIC BUILDINGS OF CITIES BY USING THE METHOD OF SYSTEM DYNAMICS - Fedoruk, Mariia; Zahvoyska, Lyudmyla (Journal of European Economy, 2018)
Using the method of system dynamics, hypotheses about functioning of the mechanism of energy saving stimulation in buildings and its ecologization tools have been proposed and tested. The results of the survey conducted by domestic and foreign experts were used as the main empirical data for analysis and modeling. The constructed simulation models have allowed to prove the advisability of using multicriteria assessment of energy saving measures effectiveness, as well as to test the recommendations we propose concerning ecologiza- tion of the energy saving process by integrating environmental and social assessments into the rules for making investment decisions. Methods of system dynamics revealed undesirable consequences and points of resistance, which can cause the failure of the proposed intervention. JEL: Q57.